Kajian Teologis Inkarnasi Kristus Berdasarkan Injil Yohanes 1: 14 - Luciana Haryanto; Yusep Yusep; Ester Yunita Dewi (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The existence of various views on the Incarnation of Christ often causes confusion. Each view provides different arguments. Therefore, a biblical study is needed to provide answers based on biblical principles. The methodology applied is exegesis. Exegesis is a way to interpret the Bible by emphasizing different approaches in the analysis of the original languages of the Bible as the main foundation. In this way, a biblical truth is obtained that can answer the various views that exist. The term incarnation comes from the Latin incarnatio which is composed of in and carnis (in the flesh). This term comes from the Greek translation “σὰρξ sarx sarcosis. Literally, σὰρξ sarcosis means to become flesh. Flesh is literally the muscular part that covers the bones of the human body. Synecdically (a figure of speech that uses a part of something to represent the whole or vice versa, to create a rhetorical or creative effect), it means the physical body as a whole flesh, which is related to the scope of the human worldly situation or mortal nature, earthly descent, blood ties, ethnic groups, and races. In general, this term gives the impression of weakness, fragility, mortality, and participation in human nature. The term σὰρξ – sarx sarcosis is closely related to the opening of the Gospel of John which reveals the word that became flesh (John 1:14). The term flesh (Greek: σὰρξ sarx) in biblical terminology refers to humans with all their anthropological dimensions. In theological terminology, The incarnation is a historical fact that explains that the invisible God, who spoke His word to humans, now clearly appeared as a human being. Jesus Christ is the Word of God who became flesh (John 1:14)